Investment Analysis on Goat and Sheep Fattening Project Based on the New Food Fermentation Farming Method (3F Method) - Ferbrianno, Erlangga; Siahaan, Uke MMP (The Indonesian Journal of Business Administration, 2012)
Goat and sheep fattening is not a popular business in Indonesia. Farmers only see this kind of business as a side income for them. The only breed 3-10 goat or sheep at one time and use traditional way in fattened the goat and sheep. This is happened because the farmer need a long time to fattened the goat and sheep, lack of capital of resources (pertanian, 2007). In order to solve the lack of capital problem, nucleus plasma is scheme can be used. This scheme can bridge the farmers (plasma) and the investors (nucleus). The farmers provide land and barn and the investors can provide another facility needed and also guiding the farmer in the fattening process. Before applying the scheme an agreement should be made between two parties about the rights and obligations of both parties, including the selling price from the plasma to the nucleus. Food fermentation farming (3F) method, a new method in goat and sheep fattening need less time, increase the goat weight fast, keep the barn not smelly try to apply in order to overcome the disadvantage in traditional method and to overcome the lack of resources problem. Investor has two places ready to run this project, Cihanjuang and Camp Hulu Cai. Investor wants to see which place is feasible and more profitable by technical analysis and investment performance analysis such as Net Present Value (NPV), Internal Rate of Return (IRR), Pay Back Period (PBP), Return on Investment (ROI), and Return on Equity (ROE). Based on technical analysis, the environment condition in Cihanjuang is not suitable because of its location near to residential area and it is also hard to find source of food. The other place, Camp Hulu Cai, is located far from residential area and near to the source of food. After the technical analysis, Camp Hulu Cai is the only suitable place for the goat and sheep fattening project. Based on the calculation of investment performance analysis its NPV is above 0, the IRR is greater than the weighted average cost of capital. In conclusion Camp Hulu Cai is the most feasible place to implement this project both technically and financially. Keywords: goat, sheep, fermentation, investment, NPV, IRR, PBP,ROE, ROI.